DIGITAL TRANSFORMATION IN IMMIGRATION SERVICES THROUGH BIOMETRIC DATA STORAGE AND PERSONAL GOVERNANCE - Waita, Rivaldo Pramudya RInaldy; Jannah, Rahmawati Nurul; Jani, Salsabila Andi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The rapid advancement of digital technology in the 21st century has ushered the world into the disruption era, a phase in which fundamental transformations across various aspects of life are inevitable. One sector that has undergone a significant transformation is immigration services, particularly through the adoption of biometric systems. Biometric technologies—including fingerprint, facial, and iris recognition, have proven effective in enhancing identification efficiency and strengthening border security. Nevertheless, the implementation of such technologies simultaneously raises critical issues regarding personal data protection and individual privacy, as biometric data are inherently unique, sensitive, and highly vulnerable to misuse if not properly safeguarded. This study seeks to examine the implications of biometric implementation in the context of Indonesian immigration, with an emphasis on its administrative benefits, potential security risks, and the relevance of legal frameworks, particularly Law No. 27 of 2022 on Personal Data Protection. Through an analytical approach, this research is expected to provide a conceptual contribution to the strengthening of digital-based immigration governance aligned with the principles of e-government, human rights protection, and public accountability in the disruption era.